Model of Treasure Island (J.C. Bardell)
Treasure Island, site of the Golden Gate International Exposition at San Francisco, as it will look when completed in 1939. This model, measured 17 by 35 feet, which required months of work by a staff of experts, is now on display in its own building in Union Square, San Francisco. In the foreground can be seen the two hangar buildings and the airport terminal now virtually completed. The main tower and six huge exhibit palaces surrounding it are also well advanced in construction.